Pharmacokinetics and Bioavailability of Doxycycline Following Parenteral Administration in Rabbits - Martínez José; Yuste María Teresa; Marín Pedro; Escudero Elisa; Badillo Elena (Acta Veterinaria)
Doxycycline, a member of the tetracycline family, is widely used in various species to treat infections caused by bacteria susceptible to this antibiotic. However, data on the pharmacokinetics of this drug in rabbits are scarce. The aim of this study was to investigate the pharmacokinetics of doxycycline after intravenous and extravascular (intramuscular and subcutaneous) administration in rabbits. A randomized crossover study (n = 5) was employed, with a dosage of 20 mg/kg. The Vss was 0.64 L/kg, indicating moderate distribution of the antibiotic in rabbits. The peak concentrations (Cmax) and the times to peak plasma concentration (tmax) obtained after extravascular administration were very similar, with not significant differences between the intramuscular and subcutaneous routes. The bioavailabilities of extravascular administrations were low (Fintramuscular=6.01 %, Fsubcutaneous=7.30 %), limiting its efficacy in the treatment of doxycycline–susceptible bacterial infections in rabbits. However, other formulations of doxycycline or other routes of administration may need to be tested to achieve better bioavailability to ensure adequate dosing regimens and clinical efficacy.